The Impact of Everolimus and Radiation Therapy on Pulmonary Fibrosis - (:unkn) unknown (My University, 2020)
Background and objectives: Everolimus (EVE) is a mammalian target of the rapamycin (mTOR) inhibitor that is widely used in cancer patients. Pulmonary toxicity, usually manifesting as interstitial pneumonitis, is a serious adverse effect of this drug. Radiation therapy, which is often administered in conjunction with chemotherapy for synergistic effects, also causes pulmonary fibrosis. In view of pulmonary damage development in these two forms of cancer treatment, we have examined the effect of EVE administration individually, in combination with radiation given in varying sequences, and its relation to the extent of pulmonary damage. Materials and Methods: We performed an experimental study in albino rats, which were randomized into five groups: (1) control group, (2) EVE alone, (3) EVE 22 h after radiation, (4) EVE 2 h after irradiation, and (5) only radiation. Sixteen weeks after thoracic irradiation, rat lung tissue samples were examined under light microscopy, and the extent of pulmonary damage was estimated. After this, we calculated median fibrosis scores in each group. Results: The highest fibrosis score was noted in Group 4. Among the five groups, the control group had a significantly lower median fibrosis score compared to the others. When the median fibrosis score of the group that received concurrent EVE with radiation therapy (RT) (Group 4) was compared with that of the control group, the difference was statistically significant (p = 0.0022). However, no significant differences were achieved among the study groups that received EVE only or RT only, whether concurrently or sequentially (p > 0.05). Conclusion: EVE is an effective treatment option for the management of several malignancies and is often combined with other therapies, such as radiation, for a more efficient response. However, an increased risk of pulmonary fibrosis should also be anticipated when these two modalities are combined, as they both can cause pulmonary damage, especially when administered concurrently.